Plastic Ball Grid Array Encapsulation Process Simulation on Rheology Effect - Dadan Ramdan; Mohd Zulkifly Abdullah; Khor Chu Yee (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2011)
The integrated circuit should be encapsulated for protection from their intended environment. This paper presents the flow visualization of the plastic ball grid array (PBGA) chip encapsulation process considering of the rheology effect. In the molding process, encapsulant flow behavior is modeled by Castro-Macosko viscosity model with considering curing effect and volume of fluid technique is applied for melt front tracking. The viscosity model is written into C language and compiled using User-Defined Functions into the FLUENT analysis. Three types of Epoxy Molding Compound namely case 1, 2, and 3 were utilized for the study of fluid flow inside the mold cavity. The melt front profiles and viscosity versus shear rate for all cases are analyzed and presented. The numerical results are compared with the previous experimental results and found in good conformity. In the present study, case 1 with greater viscosity shows the higher air trap and higher pressure distributions.